A Multidisciplinary Approach to Oncological Resections with Vascular Surgeons Improves Patient Outcomes. (August 2020) - Finlay, Ben; Bednarz, Jana; Dawson, Joe
Abstract : Objective: Oncological resections have become more radical in pursuit of disease free margins. Consequently, vascular structures may be injured inadvertently or purposely resected, with or without subsequent reconstruction. Thus, vascular surgeons have an increasing role in oncological surgery. The present authors sought to review their experience and examine the effect of timing of referral to a Vascular Surgeon (VS) on patient and surgical outcomes following tumour resection. Methods: A retrospective review was conducted of a prospectively maintained database at a public hospital network in Adelaide, Australia. All cases of collaboration between a VS and other surgeons for resection of cancer or non-malignant tumour were included. Medical records and operative, pathological, and transfusion data were reviewed, with particular attention to referring team, timing of VS referral (pre- or intra-operative), and the operative role of the VS. Results: Seventy-two cases were identified from January 2004 to June 2018. The most common collaborators were General Surgery and Urology. Of the cases, 86% were elective and 71% were referred to the VS pre-operatively. Pre-operative referral was associated with a predominant VS role of dissection and exposure. Pre-operative referral was associated with lower odds of vessel repair and reconstruction compared with intra-operative referral (adjusted OR = 0.20; 95% CI 0.04–0.93; p = .040) and a lower incidence of positive surgical margins (35% vs. 80%, p = .028). The rate of blood product units required was lower among pre-operative referrals relative to intra-operative referrals, but the effect of timing was not significant after adjustment for potential confounders (IRR = 0.80, 95% CI 0.26–2.44; p = .70). Conclusion: Pre-operative planned involvement of vascular surgery in oncological operations can improve surgical outcomes, with additional expected benefits for surgical training and cross specialty collaboration.